Feature‐driven systems engineering procedure for standardized product‐line development. Issue 6 (12th August 2021) - Granrath, Christian; Kugler, Christopher; Silberg, Sebastian; Meyer, Max‐Arno; Orth, Philipp; Richenhagen, Johannes; Andert, Jakob
Abstract: Numerous systems engineering (SE) methods for the model‐based and textual specification of systems focus on managing complexity solely by partitioning the system based on physical structures or by defining different views of the system and therefore reach their limits in agile development. The increasing demand for an agile system development requires an agile systems engineering procedure for the model‐based and textual top‐down specification of systems. Although function‐based development, variant management, and product line development are well established in software engineering, previous work has failed to introduce methods for the agile specification of systems by combining established methods from systems and software engineering. For that purpose, this paper demonstrates a new SE methodology, which for the first time combines conventional SE methods with the agile development procedure of feature‐driven development. The methodology is systematically developed based on theoretical analyses and its suitability for the application‐specific definition of feature‐driven development processes is demonstrated using the example of reference architectures for XiL simulation models of electric vehicles. By applying feature‐driven development, the resulting CUBE methodology enhances collaboration in interdisciplinary development teams and enables companies to adapt development processes to a more agile top‐down specification of systems.